(untitled) (Nonlinear Studies, 2025)
Gompertz function is widely used in data estimation of tumors, cancer and covid outbreak. We have applied Gompertz function in prey - predator model along with co-operative hunting. We calculated equilibrium points, their stability and bifurcation points around the equilibrium points, mathematically.We justify this terms by numerical simulation. Our studies reveal that the system has no Hopf bifurcation and always steady solutions.